Pelatihan Penggunaan Aplikasi Riset Inovasi (Rinov) untuk Mendorong Partisipasi Masyarakat dalam Kompetisi Liga Sinova - Baiq Rara Sinar Arian; Sofiansyah Fadli (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the understanding and skills of the community of Selebung Village, Batukliang District, Central Lombok Regency, in using the Riset Inovasi (Rinov) application as a means of registration for the Liga Sinova competition. The main problem faced by the community is the limited information regarding technical procedures and competition requirements. The implementation methods included observation, coordination with village officials, material planning, and a one-day training session. The training began with a pre-test, presentation of material from the official module, a question and answer session, practice in registering for a Rinov account, and concluded with a post-test and group photo. The evaluation results showed an increase in participants' understanding, as seen from the comparison of pre-test and post-test scores with an increase of 25%, so that participants were able to register their accounts in a more focused manner. Additionally, this activity encouraged village officials to provide follow-up assistance, ensuring the program's sustainability. Thus, this training contributed to community empowerment through the use of the Rinov application and strengthened their participation in the Liga Sinova competition.